Lexicography in the Context of Evacuation Planning Issues - Iswar Mani Adhikari (Kaumodaki: Journal of Multidisciplinary Studies, 2025)
Lexicography in evacuation planning refers to prioritizing and structuring the evacuation process in emergencies. It provides a systematic method for hierarchically addressing multiple objectives, ensuring that the most critical factors are resolved first. This work focuses on such an approach to the evacuation planning problem for the transit-based network. Lexicographically dynamic flow determines the optimal flow in a network like the maximum and minimum cost flow. The term lexicography is based on lexicographic ordering and refers to sorting or optimizing solutions in a way that respects a lexicographic priority. Such a priority can be considered based on the need of the network structures, objectives, demands, etc. Multi-objective optimization problems where secondary objectives are considered only after primary objectives are met also use such a technique.